Nanomaterial catalyzed green synthesis of tetrazoles and its derivatives: a review on recent advancements. Issue 62 (7th December 2021) - Swami, Suman; Sahu, Satya Narayan; Shrivastava, Rahul
Abstract : Tetrazoles are indispensable nitrogen containing heterocyclic scaffolds that offer a broad spectrum of applications in various domains such as medicinal chemistry, high energy material science, biochemistry, pharmacology etc. Abstract : Tetrazoles are indispensable nitrogen containing heterocyclic scaffolds that offer a broad spectrum of applications in various domains such as medicinal chemistry, high energy material science, biochemistry, pharmacology etc. Owing to their useful applications, a wide range of catalysts have been explored for green synthesis of tetrazole derivatives. In recent times, nanomaterials have been emerged as extremely efficient catalysts for different organic transformations because of their high surface area-to-volume ratio, easy surface modification, simple fabrications, easy recovery and reusability. In this article, we have presented an overview of utilization of various nano-catalysts, nanocomposites and other solid-supported nanomaterials as an efficient environmental benign catalytic system for green synthesis of tetrazoles and derivatives. This review will provide an exclusive emphasis on boehmite, magnetic, copper, carbon, MCM-41, and composite based nanomaterials that have been developed since the year 2010 for the synthesis of tetrazole derivatives. In addition, we have briefly discussed the fabrication, functionalization and characterization of some novel nanomaterials and their advantages in the synthesis of tetrazole and its derivatives along with the reaction mechanism that involves synthesis of tetrazole derivatives via nanomaterials catalysed reactions.